2021
DOI: 10.1017/s1041610221001186
|View full text |Cite
|
Sign up to set email alerts
|

Size at birth, lifecourse factors, and cognitive function in late life: findings from the MYsore study of Natal effects on Ageing and Health (MYNAH) cohort in South India

Abstract: Objective: To examine if smaller size at birth, an indicator of growth restriction in utero, is associated with lower cognition in late life, and whether this may be mediated by impaired early life brain development and/or adverse cardiometabolic programming. Design: Longitudinal follow-up of a birth cohort. Setting: CSI Holdsworth Memorial Hospital (HMH), Mysore South India. Participants: 721 men and women (55–80 years) whose size at birth was recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Some studies have shown an association between LBW and a high risk of adult mental illness (57,58). Observational evidence has shown that smaller birth size and LBW are significantly associated with cognitive and motor impairment, which have lower composite cognitive scores (β = −0.12, 95% CI[−0.19, −0.05], p = 0.001) in later life compared to those with normal BW (59)(60)(61)(62). Other results also indicate that LBW newborns exhibit developmental alterations in gene expression involved in cell differentiation, neurogenesis, and neurodegeneration (63).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown an association between LBW and a high risk of adult mental illness (57,58). Observational evidence has shown that smaller birth size and LBW are significantly associated with cognitive and motor impairment, which have lower composite cognitive scores (β = −0.12, 95% CI[−0.19, −0.05], p = 0.001) in later life compared to those with normal BW (59)(60)(61)(62). Other results also indicate that LBW newborns exhibit developmental alterations in gene expression involved in cell differentiation, neurogenesis, and neurodegeneration (63).…”
Section: Discussionmentioning
confidence: 99%
“…Limited high-quality evidence from prospective longitudinal studies is available, but collective evidence is accruing about "critical windows" in early and adult life that differentially affect risk of neurodegenerative disease and a dose–response relationship for all-cause YOD depending on number and interaction with other exposures, across the life span (Cations et al , 2019). Recent commentary published in International Psychogeriatrics (Pini and Wennberg, 2022), for example, referenced a longitudinal follow-up of a birth cohort (Krishna et al ., 2022) which found that greater size at birth was associated with better cognitive function in later live, and this was partially mediated by childhood growth and environment. Of note, there was no evidence that midlife cardiometabolic factors mediated this association.…”
mentioning
confidence: 99%
“…For example, Krishna and colleagues reported that measures associated with early cognitive development, such as birth weight, maternal educational achievement, and adult leg length, were good predictors of cognitive performance in later life (Krishna et al, 2022), a finding that is consistent with the results of studies from other emerging economies (Scazufca et al, 2008). In addition, measures of early or mid-life adversity, such as limited educational attainment and low socioeconomic status (Krishna et al, 2022;Scazufca et al, 2010), have also been associated with declining cognitive function in later life. If these factors are causally related to cognitive impairment, population-based interventions targeting them could contribute to reducing the risk of dementia in the coming decades.…”
mentioning
confidence: 99%